PEDAGOGICAL TACT AS THE BASIS OF PROFESSIONAL ACTIVITY - Razikova Lola Tuychiyevna (American Journals, 2024)
A generalized manifestation of a teacher’s communication style is a pedagogical tact, which accumulates all the components of pedagogical culture and which is one of the main indicators of pedagogical skill. K.D.Ushinskiy, who possessed a real pedagogical tact, wrote that no teacher “can ever become a good practicing teacher without tact.... No psychology is capable of replacing a person with psychological tact, which is indispensable in practice due to the fact that it works quickly and quickly... and which involves friendliness without pretense, justice without scrupulosity, kindness without weakness, order without pedantry, and, above all, constant intelligent activity.”